Fenomena Bahasa Gaul “Bestie” dan Eksistensi Bahasa Indonesia di Kalangan Remaja - Gita Sugiarti (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2022)
Language is the identity of a country or region that is used as the main communication tool. Everyone needs language when interacting, expressing ideas and opinions and other social relationships. In its development, the use of Indonesian began to shift to be replaced by the use of the language of teenagers, one of which was the use of the word bestie. The use of the word bestie is not only used by teenagers, not infrequently educated people also use this bestie language, both in oral and written form, both in formal and non-formal times, resulting in the use of language being bad and incorrect so that it will have an impact on the existence of the Indonesian language. It would be nice if we can use good and correct Indonesian, so that the existence of Indonesian as the national language is maintained. Indonesian is the language of unity, so as Indonesian people who care and respect their national language, we must maintain and help preserve our language, namely Indonesian. If we have used good and correct Indonesian, people around us will be infected directly.